Development of pure certified reference material of stevioside. (30th July 2018) - Tangpaisarnkul, Nongluck; Tuchinda, Patoomratana; Wilairat, Prapin; Siripinyanond, Atitaya; Shiowattana, Juwadee; Nobsathian, Saksit
Highlights: Pure stevioside was isolated from Stevia rebaudiana (Bertoni) leaves. Certification of purity was performed by using mass balance method and qNMR. Homogeneity of CRM was evaluated. Stability of CRM was monitored at various temperatures. Abstract: Pure stevioside was extracted from leaves of Stevia rebaudiana (Bertoni) to be used as a reference material in the instrument calibration or method validation process. The mass fraction was determined by comparison between the mass balance method and quantitative nuclear magnetic resonance (qNMR) spectroscopy. The impurities in the sample were analyzed by Karl Fischer titration for moisture content and thermogravimetric analysis for inorganic residue. Homogeneity, together with short term and long term stability, were also studied and the uncertainty was reported. The certified value of this mass fraction is 0.986 ± 0.0019 (k = 2) with 1 year stability.